2021
DOI: 10.3390/cells10082142
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Pulp Inflammation

Abstract: The dental pulp can be affected by thermal, physical, chemical, and bacterial phenomena that stimulate the inflammatory response. The pulp tissue produces an immunological, cellular, and vascular reaction in an attempt to defend itself and resolve the affected tissue. The expression of different microRNAs during pulp inflammation has been previously documented. MicroRNAs (miRNAs) are endogenous small molecules involved in the transcription of genes that regulate the immune system and the inflammatory response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 175 publications
0
8
0
Order By: Relevance
“…MicroRNAs are differentially expressed in dental pulp tissues, and they are involved in cell differentiation, proliferation and apoptosis (Munoz‐Carrillo et al, 2021). According to Maqbool et al, miRNAs such as miR‐125a‐3p, miR‐21, miR‐410 and miR‐30b were downregulated among DPC, while miRNAs such as miR‐223‐3p, miR‐146a, miR‐506, miR‐21‐5p and let‐7c‐5p were significantly upregulated among the DPC (Maqbool et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are differentially expressed in dental pulp tissues, and they are involved in cell differentiation, proliferation and apoptosis (Munoz‐Carrillo et al, 2021). According to Maqbool et al, miRNAs such as miR‐125a‐3p, miR‐21, miR‐410 and miR‐30b were downregulated among DPC, while miRNAs such as miR‐223‐3p, miR‐146a, miR‐506, miR‐21‐5p and let‐7c‐5p were significantly upregulated among the DPC (Maqbool et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In oral diseases and pathology, microRNAs are the most investigated small non-coding RNA with the highest potential to be utilized in clinical practice. MicroRNAs play a very important role in dental pulp pathology via their role in regulating the immune response and inflammation [ 46 ]. miR-21 was shown to mitigate the inflammatory signaling in LPS-stimulated dental pulp cells [ 47 ].…”
Section: Ncrnas and Oral Inflammatory Diseasesmentioning
confidence: 99%
“…Small, non-coding RNAs, namely miRNAs (18–24 nucleotides), play a vital role in regulating apoptosis by intrinsic and extrinsic pathways [ 25 ]. These molecules act post-translationally, targeting pro-and anti-apoptotic genes [ 25 , 26 , 27 ]. It was found that an overexpressed miR-761 might alleviate chronic inflammation and induce the remodelling of nasal mucosa in CRS mice.…”
Section: Introductionmentioning
confidence: 99%